TMEM182 inhibits myocardial differentiation of human iPS cells by maintaining the activated state of Wnt/β‐catenin signaling through an increase in ILK expression - Hirofumi Morihara; Shunichi Yokoe; Shigeo Wakabayashi; Shinji Takai (FASEB BioAdvances)
Abstract Transmembrane protein 182 (TMEM182) is notably abundant in muscle and adipose tissue, but its role in the heart remains unknown. This study examined the contribution of TMEM182 in the differentiation of human induced pluripotent stem cells (hiPSCs) into cardiomyocytes. For this, we generated hiPSCs overexpressing TMEM182 in a doxycycline‐inducible manner and induced their differentiation into cardiomyocytes. On Day 12 of differentiation, expression of the cardiomyocyte markers, TNNT2 and MYH6, was significantly decreased in TMEM182‐overexpressing cells. Additionally, we found that phosphorylation of GSK‐3β (Ser9) and β‐catenin (Ser552) was increased during TMEM182 overexpression, suggesting activation of Wnt/β‐catenin signaling. We further focused on integrin‐linked kinase (ILK) as the mechanism by which TMEM182 activates Wnt/β‐catenin signaling. Evaluation showed that ILK expression was increased in cells overexpressing TMEM182. These results suggest that TMEM182 maintains Wnt/β‐catenin signaling in an activated state after mesoderm formation by increasing ILK expression, thereby suppressing hiPSCs differentiation into cardiomyocytes.